2006
DOI: 10.1002/elan.200503629
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aluminum by Adsorptive Cathodic Stripping Voltammetry with 1,2‐Dihydroxyanthraquinone‐3‐Sulfonic Acid (DASA): Effect of Thin Mercury Film Electrode

Abstract: An analytical technique for aluminum (Al) based upon the complexation reaction between Al and the ligand -DASA (1,2-dihydroxy-anthraquinone-3-sulfonic acid) has previously been implemented successfully at the hanging mercury drop electrode (HMDE). There are several advantages of using mercury film electrodes (TMFE) over the HMDE, particularly if disposal of mercury is of concern. The novelty of using TMFE for adsorptive cathodic stripping voltammetry (ACSV) of Al -DASA is demonstrated in this paper. The peak p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the literature, the determination of aluminium(III) in aqueous solution by voltammetry was achieved via metal-complexation in the presence of complexing agents, such as 1,2-dihydroxyanthraquinone-3sulfonic acid (DASA) [14], alizarin S [15], alizarin violet [16], pyrogallol red [17], 8-hydroxyquinoline [18], cupferron [19], and ionophore JS-1 [20]; using thin mercury film electrodes (TMFE), renewable silver amalgam film electrodes (Hg(Ag)Fe), multi-walled carbon nanotube modified carbon paste electrodes (MWCNT/CPE), mercury electrodes, hanging mercury dropping electrodes (HMDE), HMDEs, and screen-printed carbon electrodes, respectively. Although these chelating agents have shown the capability to form a metal-complex with aluminium ions (Al 3+ ), it is desirable to use alternative materials with a stronger and more selective binding with Al 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the determination of aluminium(III) in aqueous solution by voltammetry was achieved via metal-complexation in the presence of complexing agents, such as 1,2-dihydroxyanthraquinone-3sulfonic acid (DASA) [14], alizarin S [15], alizarin violet [16], pyrogallol red [17], 8-hydroxyquinoline [18], cupferron [19], and ionophore JS-1 [20]; using thin mercury film electrodes (TMFE), renewable silver amalgam film electrodes (Hg(Ag)Fe), multi-walled carbon nanotube modified carbon paste electrodes (MWCNT/CPE), mercury electrodes, hanging mercury dropping electrodes (HMDE), HMDEs, and screen-printed carbon electrodes, respectively. Although these chelating agents have shown the capability to form a metal-complex with aluminium ions (Al 3+ ), it is desirable to use alternative materials with a stronger and more selective binding with Al 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…13,[19][20][21][22][23][24][25][26] It is also well known that AdCSV measurements have seriously drawbacks caused by interferences of organic compounds present in samples of complex matrices. In this work, we observed that the determination of Al, Cr, and Ni by AdCSV directly in diluted (1:10) EPO samples was not possible.…”
Section: Determination Of Al Cr and Ni By Adcsv In Epo Samplesmentioning
confidence: 99%
“…34,35 These sensors, however, suffer from different drawbacks: low sensitivity or precision, use of mercury electrodes, sensitivity to interfering species and none of them can be selectively deposited on microarrays electrode. 23,25,26,28,[31][32][33][36][37][38] Most of them were designed for (i) Al(III) sensing in acidic conditions 23,27,28,[32][33][34][35] and/or (ii) in physiological conditions but in the absence of serum proteins. 25,26,29 Here, we report for the first time an application of electrochemically assisted self-assembly to form a complex supramolecular hybrid thin film composed of a biodegradable and non-toxic molecules, metal ions and metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%